The effect of caffeinated carbohydrate-electrolyte solutions on substrate metabolism, caffeine excretion and time trial cycling performance. - Kovacs, E.; Stegen, J.; Brouns, F. (APS Manuskript, 1998)
The effect of different dosages of caffeine (CAF) in combination with a carbohydrate-electrolyte solution (CES) on time trial (TT) cycling performance was examined. In a randomized, double-blind, cross-over design, fifteen well-trained cyclists ingested a water placebo, a 7% CES drink or a 7% CES with one of three dosages of CAF (150, 225 and 320 mg.L-1). When starting a warm-up protocol of 20 min, the subjects ingested 8 mL.kg-1 body weight of drink. After approximately 35 min, they performed a TT of about 1 h, and ingested 3 mL.kg-1 body weight of drink on achieving 1/3 and 2/3 of TT. Total fluid intake was identical for all treatments and amounted 1025+/-26 (mean+/-SE) mL. CAF intake amounted 2.1, 3.2 and 4.5 mg.kg-1 BW for CES-150, CES-225 and CES-320, respectively. A significant improvement in TT performance was observed when CAF was added to the CES. The mean performance times for the water placebo and the CES without CAF were 62.5+/-1.3 min and 61.5+/-1.1 min, respectively. The performance enhancing effect of CAF was already apparent at the lowest dosage of 150 mg.L-1 (60.4+/-1.0 min), and was stronger with 225 mg.L-1 (58.9+/-1.0 min). A dosage of 320 mg.L-1 CAF, however, did not result in a further improvement (58.9+/-1.2 min). The consumption of different drinks resulted in significant differences in plasma substrates. With water placebo the increase in plasma FFA and glycerol was most pronounced, ruling out that the effect of CAF on performance may be explained by increased lipolysis and FFA availability. CAF containing drinks significantly increased plasma lactate values in line with higher work output. The addition of CAF in the dosages examined resulted in urinary CAF concentration below the doping level of the International Olympic Committee (12 _g.mL-1) in all subjects. The mean urinary CAF concentrations after exercise were 1.3+/-0.2, 1.9+/-0.2 and 2.5+/-0.2 _g.mL-1 for 150, 225 and 320 mg.L-1. Regional sweat sampling revealed that sweat CAF concentration was highly correlated to plasma CAF concentration (r=0.98). Urinary CAF concentration was dosage-related and highly correlated to CAF concentration in plasma and sweat (r=0.92). Sweat CAF excretion during exercise exceeded post-exercise early void urinary CAF excretion. Furthermore, CAF ingestion resulted in a small increase in urinary Mg2+ and Ca2+ excretion. This was compensated by the electrolyte content of the drink. Water placebo ingestion, however, induced a net Mg2+ and Ca2+ loss. Urine production was not influenced by CAF. It is concluded that the addition of low amounts of CAF to CES had an ergogenic effect on TT performance of about 1 h. Diuresis was not promoted by CAF ingestion and urinary CAF concentration remained widely below the doping level in all individuals. s. a. J. Appl. Physiol. Vol. 85, Issue 2, 709-715, August 1998